A Stored Charge Model for the Sodium Channel - Hoyt, Rosalie C. (1971)
A new model is proposed to account for the apparent conductance changes of the sodium, or early, channel in nerve fiber membranes. In this model it is assumed that the channels are gated at the interior side of the membrane and are resistively limited at the exterior side by sodium selective barriers of high resistance to ion flow. Under resting conditions the closed channels accumulate a store of sodium ions, dependent on the exterior sodium concentration. With the application of a depolarizing clamp the interior gates open allowing the stored ions to discharge into the interior low sodium concentration solution. In this model the initial rise in the early current results from the opening of more and more gates in response to the depolarizing clamp. The subsequent fall in the early current results from the “capacitative” discharge of the opened channels, limited by the high resistive barrier at the exterior end. Upon repolarization, the gates reclose and sodium ions reaccumulate in the channels from the high concentration external solution, but at a slow rate determined by the resistive barrier. Preliminary tests of this model, using a number of simplifying assumptions, show that it has the ability to account, at least semiquantitatively, for the major characteristics of the experimental clamp results.